Avaliação da interferência mineralógica em métodos de análise de Zn em amostras de natureza silicatada oriundas da Mina e da Usina de Vazante - MG - Fernando Oliveira Tartarotti (2022)
Zinc, a metal currently mined from several deposits around the world, has its main occurrence in sulfide deposits, however, silicated deposits like Vazante have been successfully mined showing high relevance from a strategical and economical point of view. As a singular deposit, analytical questions must be observed with extreme detail, not only in exploration phases but also while mining processing and commercializing. Two analytical methods by wet route, one including four acids to digestion (HCl+HNO3+HClO4+HF) another including two acids (HCl+HNO3) besides fused bead / x-ray fluorescence were considered after a detailed mineralogical characterization. In each method the weight of sample to be analyzed was changed and all determinations were conducted in triplicate. The samples, divided into four main groups, show small differences in mineralogical composition inside the groups but very significant differences among the groups. Certified reference material prepared by own matrix were applied to help evaluate the accuracy. The most consistent results were obtained from 4- acid digestion method despite x-ray fluorescence had presented low variability in a general way.